The characterisation of the uptake of microparticulates across intestinal lymphoid tissue - Howard, Kenneth Alan (1994)
Poly(lactide-co-glycolide) (PLG) biodegradable microparticles were evaluated as an oral delivery system for immunisation against equine influenza virus. Model particulates (fluorescent polystyrene and gold labelled polystyrene) were used to characterise the route and mechanism of intestinal uptake. Peyer's patches were found to be the site of particulate intestinal absorption characterised by phagocytosis at the M cell surface. Microparticles were found within intercellular compartments indicating a paracellular route for the transit of microparticles from lumen to lymph. A quantitative method of counting the number of microparticles passing into the lymph in both the superior mesenteric and thoracic lymph ducts indicated levels of intestinal uptake high enough to deliver vaccines via this route.